Pseudo-Temporal Analysis of Single-Cell RNA Sequencing Reveals Trans-Differentiation Potential of Greater Epithelial Ridge Cells Into Hair Cells During Postnatal Development of Cochlea in Rats - Chen, Jianyong; Gao, Dekun; Chen, Junmin; Hou, Shule; He, Baihui; Li, Yue; Li, Shuna; Zhang, Fan; Sun, Xiayu; Jin, Yulian; Sun, Lianhua; Yang, Jun (Frontiers in Molecular Neuroscience, 2022)
The hair cells of the cochlea play a decisive role in the process of hearing damage and recovery, yet knowledge of their regeneration process is still limited. Greater epithelial ridge (GER) cells, a type of cell present during cochlear development that has the characteristics of a precursor sensory cell, disappear at the time of maturation of hearing development. Its development and evolution remain mysterious for many years. Here, we performed single-cell RNA sequencing to profile the gene expression landscapes of rats’ cochlear basal membrane from P1, P7, and P14 and identified eight major subtypes of GER cells. Furthermore, single-cell trajectory analysis for GER cells and hair cells indicated that among the different subtypes of GER, four subtypes had transient cell proliferation after birth and could transdifferentiate into inner and outer hair cells, and two of them mainly transdifferentiated into inner hair cells. The other two subtypes eventually transdifferentiate into outer hair cells. Our study lays the groundwork for elucidating the mechanisms of the key regulatory genes and signaling pathways in the trans-differentiation of GER cell subtypes into hair cells and provides potential clues to understand hair cell regeneration.